Rehabilitación complejo arquitectónico Monumento Nacional Edificio de Bellas Artes Curiplaya Florencia – Caquetá (2021)
The project addressed in this monograph is a rehabilitation of a cultural heritage asset, in the city of Florencia Caquetá, the property is located in the center of the city; towards the years 1945, he commissioned the design and construction to the architect Eduardo Ferreira; During this time it served as a port for unloading and shipping merchandise such as rubber, as well as passengers traveling to and from Florence, communicating through the Orteguaza River with municipalities in the center and south of the department.